Research on the Influence of Cycloid Gear Installation Deviation on Tooth Surface Error - Wei, Qinglei (International Journal of Mechanical and Electrical Engineering, 2026)
To investigate the influence of workpiece-tool position errors on the tooth surface during the grinding of RV reducer cycloidal gears using a worm wheel, the study is based on meshing theory. Starting from the tooth profile equation of the worm wheel's normal cross-section, the meshing equation for grinding cycloidal gears with the worm wheel is derived. By introducing coordinate transformation matrices that account for installation angle deviations of the worm wheel, eccentricity of the cycloidal gear workpiece, and flatness deviations, the tooth surface equation of the cycloidal gear under error conditions is calculated. The correctness of the theory and analysis is verified through VERICUT grinding simulation. Through comparative analysis, the impact patterns of various errors on the tooth surface are obtained, which can provide a theoretical basis for error compensation in the grinding of cycloidal gears.